Analysis of Protein Content on Commercial Protein Supplement in Indonesia - Mury Kuswari; Nazhif Gifari; Rachmanida Nuzrina; Suci Justickarin; Anni Fathiya; Falik Hutasuhut (STKIP Muhammadiyah Kuningan, 2021)
Commercial Protein Supplements that are circulating freely nowadays are consumed not only by athletes but the wider community, especially sports activists who rely upon it to improve performance or merely for aesthetic interests. This study aims to analyze the nutritional content of the five supplements circulating freely in Indonesia to then compare it with the claims on the packaging label. We analyzed five samples of popular supplements in Indonesia obtained online and then tested in three copies for each sample. The actual total protein in the supplement sample is measured using the Kjeldahl method where the appropriate nitrogen material is converted to percentage of protein by multiplying a factor of 6.38 in duplicate. Then the research data processed and analyzed using Microsoft Excel 2016 computer programs then by Statistical Program for Social Sciences (SPSS), consecutively. Relationships between different tests were evaluated by calculating the relevant correlation coefficients (Pearson linear correlation) (p <0.05). Analysis of variance (ANOVA) was used to compare the differences between products with different manufacturing processes (p <0.05). Based on the analysis results, only two of the five samples studied has a minimum of 80% compatibility with the claim on the packaging label. Several main factors including inaccurate analysis, preparation processing on products that triggers protein denaturation, inadequate storage, and regulations that have just been set so that producers are still free to write Nutrition Value Information with a fairly low level of accuracy. This research is expected to be able to help the evaluation for producers and the government (BPOM) to be able to provide correct information to consumers so that maximum physiological benefits can be obtained.